Relationship among corporate reporting, corporate governance, going concern and investor confidence: Evidence from listed banks in sub Saharan Africa - Paul Hammond; Mustapha Osman Opoku; Paul Adjei Kwakwa (Cogent Business & Management, 2022)
A vibrant financial sector has a lot to offer towards the growth and development of an economy. It is in this regard that investor confidence matters most to the sector. Although the financial sector in the sub-Saharan African region is still growing, there are some crises in the sector that have made going concern an important matter for stakeholders. It is expected that, as often argued, corporate reporting and corporate governance can improve performance in order to boost investors' confidence. However, the interrelationship between corporate reporting, corporate governance, going concern, and investor confidence has not been investigated yet in the sub-region for the fiancial sector. This study analysed the relationship among corporate reporting, corporate governance, going concern, and investor confidence for banks in the sub-region. Data were collected from published financial statements of selected financial banks in Ghana, Nigeria, and South Africa using data ranging from 2011 to 2020. The Partial Least Square Structural Equation Modeling (PLS-SEM) was used to analyse the data and it revealed that going concern relates positively to investor confidence. Also, corporate reporting and governance directly affect investor confidence. The implication is that management should enhance and disclose the corporate governance mechanisms of financial institutions in order to improve their ability to continue operations and increase investor confidence.
Keywords: 650; financial crisis; corporate governance; going concern; investor confidence; reporting